Planting a seed - child health care nurses' perceptions of speaking to parents about overweight and obesity: a qualitative study within the STOP project - My Sjunnestrand; Karin Nordin; Karin Eli; Paulina Nowicka; Anna Ek (BMC, 2019)
Abstract Background Nurses in child health care (CHC) centers in Sweden play a key role in the early detection and management of childhood overweight/obesity, through meeting families early, regularly and over many years. However, research focusing on CHC nurses' perceptions of their role in childhood overweight/obesity management is scarce. As part of the EU-funded project "Science and Technology in childhood Obesity Policy" (STOP), this study examines CHC nurses' perceptions of speaking to parents about children's overweight/obesity and of their role in referring children to treatment for overweight/obesity. Methods All registered CHC nurses in Stockholm County (n = 442) received an email invitation letter explaining the study. Individual face-to-face visits (n = 15) in selected centers, and phone calls (n = 24) to nurses working in these centres were also conducted. In total, 17 CHC nurses (all female, average work experience 6.7 years (SD ± 4.9 years)) from 10 municipalities (including four of the top five municipalities with the highest prevalence of overweight and obesity) in Stockholm County were interviewed. The interviews were conducted by phone, transcribed and analyzed using thematic analysis. Results Two main themes were developed through the analysis: 1) The relationship between the nurse and the parent and 2) Glitch in the system. Under the first theme, nurses reported that weight-related discussions were facilitated by building and maintaining trust with parents. However, nurses also said they were reluctant to address children's weights if this could compromise parents' trust. Under the second theme, nurses highlighted several organizational barriers to addressing a child's weight with parents, including insufficient cooperation with other healthcare providers and limited time for visits. Nurses also identified lack of sufficient knowledge about what to offer the family and lack of confidence in their communication skills as additional barriers. Conclusions We found that pediatric nurses perceive relational and organizational factors as barriers to address childhood obesity with parents. To improve care, it is necessary to provide nurses with continuing education about obesity and communication skills and organizational support to improve communication within the healthcare system. Trial registration ClinicalTrials.gov NCT03800823; 11 Jan 2019, prospectively registered.